Pengaruh Kepemimpinan Transformasional Dan Disiplin Kerja Terhadap Kepuasan Kerja Pegawai (Studi Kasus Kantor DPRD Kota Bima) - Arif Akbarrurrijal; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Transformational leadership is the ability of a leader to influence employees to achieve targeted goals to do extraordinary things. A leader must be able to influence his employees in certain ways to achieve the goals to be achieved from the company. Transformational leadership is the ability of superiors to work with others to optimally transform human resources within the company to achieve goals in accordance with predetermined achievements.Transformational leadership has a strong influence in running an organization. A leader must be able to create a sense of self-confidence with employees, as a leader must also be able to make the employees he leads have the determination to carry out the goals that have been determined by the company. Leaders should involve employees when making decisions, so that employees feel more valued and have self-esteem. Transformational leadership is a situation in which employees of a transformational leader feel trust, admiration, loyalty, and respect for the leader, and they are motivated to do more than expected. A leader must be able to transform and motivate employees by making them more aware of the importance of results or work, encouraging them to prioritize the company or team over self-interest, and activating their needs at a higher level. The leadership style applied by the leader will have an impact on employee job satisfaction. Job satisfaction is a positive emotional state that is the result of evaluating one's work experience. Job dissatisfaction arises when one's expectations are not met. (Danang Sunyoto 2015) Work discipline can be defined as an attitude of respect, respect, obedience, and obedience to the applicable regulations, both written and unwritten and being able to carry out them and not evading sanctions. Employee discipline is absolutely necessary so that all activities that are being carried out run according to the mechanism that has been determined by Rivai, (2009) Good job satisfaction must be supported by high employee discipline, especially seen from the level of employee attendance. According to Wijaya et al. (2012: 52), the average attendance rate is 2-3 percent, symptoms of poor employee work discipline. Basically the discipline factor is one of the important functions of human resource management and is the key to the realization of goals, because without discipline it is difficult to achieve maximum goals. Job satisfaction is an assessment, feeling or attitudea person or employee towards his work and relationships with the work environment, type of work, compensation, relationships between coworkers, social relations at work and so on. Job satisfaction is the fulfillment of several wants and needs through work or work activities. Each employee will have a measure of job satisfaction which varies from one employee to another. Job satisfaction varies due to differences social status in society. Keywords : Transformational leadership, work discipline and job satisfaction